Family Labor Contribution To Vegetable Farming Income Of Rainfed Lowland Fields In Central Bengkulu Regency - Wawan Eka Putra; Satria Putra Utama; Agus Purwoko (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
Labor, whether within and outside family member, has animportant contribution in the structure of farm costs. Thisstudy aims to analyse the contribution of family labor tovegetable farming with four different cropping patterns inrainfed lowland land and its effect on farming profits. Theresearch was conducted in Pondok Kelapa District, BengkuluTengah Regency from May to October 2019. There are sixvegetable cropping patterns in Pondok Kelapa District,namely (1) cucumber - paria - long beans, (2) cucumber -gambas - long beans, ( 3) cucumber - long beans - longbeans, (4) long beans - pariah - long beans, (5) long beans -luffa - long beans, and (6) long beans - long beans - kalepulled - pulled kale. Data were collected through a census of50 vegetable farmers and analyzed descriptively using thestructure of farm costs and the R/C ratio. The results showedthat the contribution of labor costs from within the family tothe six cropping patterns was between 38.84 - 61.36% withan R/C ratio between 1.55 - 1.94. The highest laborcontribution was obtained in cropping pattern 6, namely61.36% with the lowest R/C ratio value of 1.55. However, ifthe family labor cost is assumed not to be taken into accountthe farm input costs, then the R/C ratio value in croppingpattern 6 is the highest, which is 4.06.